TECHNO-ECONOMIC ANALYSIS OF THE POTENTIAL FOR HYBRID POWER PLANT IN GUNUNG SEWU GEOPARK, PACITAN REGENCY - Prima, Putri; Setiawan, Ahmad Agus; Dewayanto, Nugroho (Master in Systems Engineering, 2025)
Gunung Sewu has been designated as a Global Geopark Area by The United Nations Educational, Scientific and Cultural Organization (UNESCO) in 2015. In the preparation of the Gunung Sewu Masterplan as a UNESCO Global Geopark (UGGp), the provision of environmentally friendly and sustainable electricity is one of the strategies to utilize the renewable energy. The application of Hybrid Power Plants (HPP) that utilize wind and solar energy in the industrial and tourism sectors can have a positive impact on regional income where economic growth is one of the strategic issues of Pacitan Regency.The average wind speed in Pacitan is 3.41 m/s and the average solar radiation reaches 5.69 kWh/m2/day so that it can be said that the potential for solar and wind energy in the Gunung Sewu Pacitan Geopark is reliable and feasible to be used as an environmentally friendly energy source. The simulation of HPP that will be implemented at Buyutan Beach illustrates that the system could produce an output of 7,519 kWh/yr. This result is able to meet the annual demand of 4,107 kWh/yr and even exceed the annual requirement.The economic analysis of the simulated HPP system produces a negative Net Present Value (NPV). This could be due to the large value of Operational Expenditure (OpEx) and Capital Expenditure (CapEx) and the low purchase price (National Electricity Company’s feed in tariff). However, this research also proposes a scenario so that the HPP system can still be applied by dividing the cost components contained in the budget plan into two parts. In the proposal obtained cash inflows of Rp. 8,640,834.80/year and a positive or feasible NPV.